Clinical, biochemical and pathological study of Egyptian pediatric patients with mitochondrial diseases - Mohamed Mahmoud Moustafa; Gina Assad Nakhla; Laila Abdelmottelib Selim; Rudy Van Coster (Cairo : Mohamed Mahmoud Moustafa, 2014)
Mitochondrial diseases encompass a large group of disorders with protean clinical manifestations. They can present at any age with any clinical feature, so clinician's high index of suspicion must be present for proper diagnosis of these disorders. Morava et al. (2006) criteria depending on clinical, biochemical, imaging and pathological features of muscle biopsy represent a good diagnostic tool for diagnosis of mitochondrial diseases in children with high specificity. Enzyme complex measurements by spectrophotometry can be used for confirming diagnosis of the underling mitochondrial disorder. We used Morava criteria (2006) to diagnose our 20 Egyptian children presenting with manifestations of suspected mitochondrial disorders, and we diagnose 15 (75%) patients as definite mitochondrial disorder, 10 cases of them proved to have complex (es) deficiency (ies) with enzyme measurements using spectrophotometry in ghent university
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Metabolic; Mitochondrial; Pediatric